2023
DOI: 10.1093/ndt/gfad003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cold HD for the prevention of HD hypotension and mortality in the general HD population

Abstract: Background Cold hemodialysis (HD) prevented intra dialysis hypotension (IDH) in small, short term, randomized trials in selected patients with IDH. Whether this treatments prevents IDH and mortality in the HD population at large is unknown. Methods We investigated the relationship between dialysate temperature and the risk of IDH, i.e. nadir BP <90 mmHg, (GEE model) and all cause mortality (Cox's regression) in an inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…As for the second and third finding, our study confirms and extends previous data on T b and thermal perception 11,13,19 . Both the recently published MyTemp study on the use of personalized cooler dialysate 11 and a lately published large retrospective analysis, 12 demonstrated comparable results in terms of cold sensations, but differed methodologically from the present investigation. In these studies, the difference in dialysate temperature between cool and standard HD(F) was 0.6 and 0.5°C, respectively, versus 1.0°C in our study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As for the second and third finding, our study confirms and extends previous data on T b and thermal perception 11,13,19 . Both the recently published MyTemp study on the use of personalized cooler dialysate 11 and a lately published large retrospective analysis, 12 demonstrated comparable results in terms of cold sensations, but differed methodologically from the present investigation. In these studies, the difference in dialysate temperature between cool and standard HD(F) was 0.6 and 0.5°C, respectively, versus 1.0°C in our study.…”
Section: Discussionsupporting
confidence: 85%
“…8 An observational study even suggested that cHD is not only associated with a lower mortality risk than sHD, but also with promising effects on physical functioning and general health. 9,10 Yet, as neither a recent cluster-randomized trial nor a lately published retrospective analysis in >8000 patients could confirm this finding, 11,12 and cHD has been associated with burdensome cold sensations, 13 the combination of uncertain health effects and adverse symptoms may constrain health-care workers from advising cHD as dialysis modality of first choice.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible the absence of effectiveness in the MyTEMP study may relate to the sample population under investigation (prevalent patients) rather than the intervention in question. In a large observational study of over 8000 incident dialysis patients, Zoccali et al found a 0.5°C reduction in dialysate temperature was associated with a 33% reduction ( P < 0.001) in the risk of IDH when utilizing a case-mix, facility-level adjusted analysis [36 ▪▪ ]. There was no impact on all-cause mortality [36 ▪▪ ].…”
Section: The Mytemp Studymentioning
confidence: 99%
“…In a large observational study of over 8000 incident dialysis patients, Zoccali et al found a 0.5°C reduction in dialysate temperature was associated with a 33% reduction ( P < 0.001) in the risk of IDH when utilizing a case-mix, facility-level adjusted analysis [36 ▪▪ ]. There was no impact on all-cause mortality [36 ▪▪ ]. Personalizing cooled dialysate to the individual clinical need, rather than just to degree of temperature reduction in relation to predialysis body temperature as with the MyTEMP study, offers an effective and easy-to-implement management strategy for confirmed IDH and symptomatic haemodynamic instability during haemodialysis.…”
Section: The Mytemp Studymentioning
confidence: 99%
“…Much more robust data became available after the publication of a recent observational study that included 8071 patients receiving maintenance dialysis in 103 clinics in Portugal and Spain. 10 In unadjusted models, over a median observational period of 13.6 months, a decrement of 0.5°C in the dialysate temperature was associated with a small decrease of 2.4% in the risk of intradialytic hypotension (odds ratio [OR]: 0.976; 95% CI: 0.957-0.995). In case-mix, facility-level adjusted analysis, the use of cooler dialysate temperature was associated with a substantially higher reduction of 33% in the risk of intradialytic hypotension (OR: 0.67; 95% CI: 0.63-0.72).…”
mentioning
confidence: 99%